Implementation of Extracurricular Programs in Enhancing Students’ Talents and Interests at SMA Negeri 26 Halmahera Selatan, North Maluku Province - Suldin Munir; Romi J. Mongdong; Zoya F. Sumampow (International Journal of Information Technology and Education, 2026)
Extracurricular programs constitute a vital component of holistic education, providing students with structured opportunities to develop talents, interests, and character traits that formal classroom instruction alone cannot fully cultivate. However, the effectiveness of such programs hinges on sound implementation, adequate facilities, and committed institutional support, challenges that are particularly pronounced in schools situated in geographically remote or resource-limited areas. This study aimed to analyze the implementation of extracurricular programs in enhancing the talents and interests of students at SMA Negeri 26 Halmahera Selatan, North Maluku Province, Indonesia. A qualitative approach with a descriptive design was employed. Data were collected through in-depth interviews, direct observation, and document analysis involving the school principal, vice-principal for student affairs, extracurricular supervisors, and students. Data analysis followed the Miles and Huberman model, comprising data reduction, data display, and conclusion drawing, with triangulation of sources and techniques applied to ensure trustworthiness. Findings revealed that extracurricular implementation was carried out through three systematic stages: planning, execution, and monitoring. The school functioned as a facilitator by providing dedicated time and policy support, while extracurricular supervisors played a pivotal role in guiding, training, and motivating students. Student participation was predominantly positive, driven by intrinsic interest and the social learning opportunities offered by extracurricular activities. Nevertheless, implementation was constrained by limited facilities and time allocation, as well as geographical barriers affecting student attendance consistency. Extracurricular programs at SMA Negeri 26 Halmahera Selatan yielded meaningful positive impacts on student talent development, self-confidence, and social skills, demonstrating that committed human resources and collaborative management can offset resource limitations. Schools in resource-constrained and geographically remote settings should prioritize relational, mentorship-based approaches in extracurricular management as a viable strategy for optimizing student potential development.